2013
DOI: 10.1371/journal.pone.0054813
|View full text |Cite
|
Sign up to set email alerts
|

Two Functional Motifs Define the Interaction, Internalization and Toxicity of the Cell-Penetrating Antifungal Peptide PAF26 on Fungal Cells

Abstract: The synthetic, cell penetrating hexapeptide PAF26 (RKKWFW) is antifungal at low micromolar concentrations and has been proposed as a model for cationic, cell-penetrating antifungal peptides. Its short amino acid sequence facilitates the analysis of its structure-activity relationships using the fungal models Neurospora crassa and Saccharomyces cerevisiae, and human and plant pathogens Aspergillus fumigatus and Penicillium digitatum, respectively. Previously, PAF26 at low fungicidal concentrations was shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 53 publications
(91 reference statements)
3
40
0
Order By: Relevance
“…Some of these granules presented strong red labeling. These observations are fully consistent with previous data describing the interaction, internalization, and killing produced by PAF26 on P. digitatum, N. crassa, and S. cerevisiae (Harries et al 2013;Muñoz et al 2006Muñoz et al , 2012Muñoz et al , 2013b.…”
Section: Paf102 Is Internalized By Fungal Cells In An Energy-dependensupporting
confidence: 92%
See 3 more Smart Citations
“…Some of these granules presented strong red labeling. These observations are fully consistent with previous data describing the interaction, internalization, and killing produced by PAF26 on P. digitatum, N. crassa, and S. cerevisiae (Harries et al 2013;Muñoz et al 2006Muñoz et al , 2012Muñoz et al , 2013b.…”
Section: Paf102 Is Internalized By Fungal Cells In An Energy-dependensupporting
confidence: 92%
“…Our study shows that the kinetics of the interaction and killing of F. proliferatum by PAF102 (Figs. 6 and 7) is markedly similar to that of P. digitatum or N. crassa by PAF26 (Muñoz et al 2012(Muñoz et al , 2013b. Therefore, increase of activity is likely a consequence of the molar increase of physically linked AMP units per molecule of peptide, and not of any significant change in the mechanism of action.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…It has been shown that PAF26 is an antifungal cell-penetrating peptide that first interacts with the outer CW of fungi and that CW protein genes determine its activity toward S. cerevisiae (31,38,41). Since flor yeast strains offer a natural diversity of CW-related phenotypes associated with the abundant Flo11 protein, we decided to test the effect of PAF26 on a number of S. cerevisiae flor strains with distinct genetic backgrounds, lengths, and structure of FLO11 gene and capabilities to form biofilm (see Materials and Methods) (14).…”
Section: Resultsmentioning
confidence: 99%